Platelet functional and transcriptional changes induced by intralipid infusion - Beaulieu, Lea M.; Vitseva, Olga; Tanriverdi, Kahraman; Kucukural, Alper; Mick, Eric; Hamburg, Naomi; Vita, Joseph; Freedman, Jane E. (Thrombosis and Haemostasis, 2016)
Multiple studies have shown the effects of long-term exposure to high-fat or western diets on the vascular system. There is limited knowledge on the acute effects of high circulating fat levels, specifically on platelets, which have a role in many processes, including thrombosis and inflammation. This study investigated the effects of acute, high-fat exposure on platelet function and transcript profile. Twenty healthy participants were given an intravenous infusion of 20% Intralipid emulsion and heparin over 6 hours. Blood samples were taken prior to and the day after infusion to measure platelet function and transcript expression levels. Platelet aggregation was not significantly affected by Intralipid infusion, but, when mitochondria function was inhibited by carbonyl cyanide 3-chlorophenylhydrazone (CCCP) or oligomycin, platelet aggregation was higher in the post-infusion state compared to baseline. Through RNA sequencing, and verified by RT-qPCR, 902 miRNAs and 617 mRNAs were affected by Intralipid infusion. MicroRNAs increased include miR-4259 and miR-346, while miR-517b and miR-517c are both decreased. Pathway analysis identified two clusters significantly enriched, including cell motility. In conclusion, acute exposure to high fat affects mitochondrial-dependent platelet function, as well as the transcript profile.
Keywords: Clinical studies; gene expression; platelet physiology; obesity